6H-[1, 2, 5]Thiadiazolo[3, 4-e]thieno[3, 2-b]indole-flanked para-azaquinodimethane based aromatic-quinoidal polymer semiconductors with high molecular weights synthesized via direct arylation polycondensation. Issue 8 (30th March 2023) - Xiao, Yufa; Fu, Huaijie; Li, Zefeng; Zheng, Yingxuan; Deng, Ping; Lei, Yanlian; Yu, Yan
Abstract : The 6 H -[1, 2, 5]thiadiazolo[3, 4- e ]thieno[3, 2- b ]indole-flanked para -azaquinodimethane ( p -AQM)-based polymer semiconductors PQ-1 and PQ-2 are rationally designed through a π-extended aromatic-quinoidal design strategy. Abstract : The 6 H -[1, 2, 5]thiadiazolo[3, 4- e ]thieno[3, 2- b ]indole-flanked para -azaquinodimethane ( p -AQM)-based polymer semiconductors PQ-1 and PQ-2 are rationally designed through a π-extended aromatic-quinoidal design strategy. They are synthesized by the direct arylation polycondensation (DArP) method. Their physicochemical properties are investigated. Both polymers show high number-average molecular weights of over 120 kDa. PQ-1 exhibits a narrower band gap compared to its thiophene-flanked p -AQM polymer counterpart. PQ-2, with more aromatic thiophene units in the conjugated main chains, displays a broader band gap compared to PQ-1 . Both PQ-1 and PQ-2 possess high-lying highest occupied molecular orbital energy levels (about −5.0 eV). They exhibit typical p-type semiconductor characteristics according to the results of characterization of organic field-effect transistors. This work presents an alternative π-extended aromatic-quinoidal design strategy and a convenient DArP method to build new p -AQM polymer semiconductors.